An investigation into over indebtedness in South Africa with a focus on the Western Cape Province - Bibby, Penny (Department of Finance and Tax, 2014)
This study aims to present an analysis of the literature on the nature and causes of over indebtedness by studying all surveys related to over indebtedness among urban South African households with a focus on consumers in the Western Cape in order to answer the research question "who is most likely to be over indebted and what are the main variables that explain this risk" and how does the debt levels in South Africa compare to that of the UK, USA, Australia and Canada.